El as the speaking voice in Psalm 82:68 - Frankel, David (The journal of Hebrew scriptures, 2010)
YHWH is usually understood to play two roles in Psalm 82: that of prosecutor of the gods (vv 2–5) and that of high judge who convicts the gods to death (vv 6–7). This article suggests that the role of the high judge is played not by YHWH but by El. YHWH serves as prosecutor of the gods in El's court. In this reading YHWH speaks only in vv 2–5. In vv 6–8 El offers his verdict, after hearing the testimony of YHWH against the gods. After sentencing the gods of his council to death (vv 6–7), El appoints YHWH to rule the world in their place (v 8).